MARKETING POLÍTICO E A REELEIÇÃO DE FERNANDO HENRIQUE CARDOSO: um estudo sobre a comunicação durante a campanha nas páginas da revista Veja em 1998 - Brogio, Thybor Malusá (2011)
This thesis aims, through quantitative and qualitative content analysis, to further our understating how Veja magazine covered Fernando Henrique Cardoso election in 1998, and how his public image was formed through its publications from June to October of that year, which Fernando Henrique was elected in the first round, analyzing whether the magazine Veja has given more credit to FHC rather than to his opponents. In order to increase the knowledge about the subject, we studied the world behind political propaganda, ideological and political marketing, and also the magazines historical ideological values. Thus, it was concluded that the magazine during the period analyzed, has published more articles on Fernando Henrique Cardoso rather than any presidential candidate in 1998, always considering him as the best to govern the country, that time. Any material published significantly strengthened FHCs influence on Veja s readers, which has favored him during the campaign.